A Critical Gadamerian Review of M. Syuhudi Ismail's and Muhammad Syahrur's Readings of the Hadith on Female Leadership - Ariangga Ramadhansyah; Masruhan; Fairuz Zakirah (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2026)
The hadith of Abu Bakrah on the prohibition of female leadership (Sahih al-Bukhari nos. 4425 and 7099) has become a battleground for competing paradigms in contemporary hadith hermeneutics. M. Syuhudi Ismail classifies it as a temporal-local hadith, thereby opening space for female leadership across all public domains; Muhammad Syahrur, through the framework of al-sunnah al-nabawiyyah and the theory of al-hudud, positions such hadiths as products of the Prophet's historical ijtihad that are not absolutely binding. This article examines both readings through the philosophical hermeneutics of Hans-Georg Gadamer, particularly the concepts of Vorurteil (prejudice), Wirkungsgeschichte (history of effect), and the rehabilitation of authoritative tradition. The study is library research employing a descriptive-analytical-critical method, drawing on primary hadith sources, classical commentaries (especially Fath al-Bari), the works of both figures, and recent secondary literature from the past decade. The findings are threefold. First, Syahrur performs a prejudice against prejudice, precisely what Gadamer rejects as Enlightenment dogmatism. Second, Syuhudi's temporal-local classification lacks operational criteria that would distinguish it from the imposition of a contemporary horizon upon the text. Third, a more defensible reading, both hermeneutically and according to the manhaj al-muhaddithin, situates the commentarial tradition as a productive Wirkungsgeschichte while preserving the classical distinction between al-wilayah al-uzma and other forms of women's public roles.